Thinking Narratively Between Novel-Essay and Narrative Essay - Fusillo, Massimo; Simonetti, Gianluigi; Marchese, Lorenzo (Transcodification: Arts, Languages and Media, 2022)
What is the connection between philosophical enquiries and storytelling in contemporary narrative? Is it possible to outline some features of a so-called philosophical fiction in Western literature throughout the last two centuries? This book aims to provide multi-disciplinary insight on this long-standing issue and to give a plural answer, hosting extensive essays by seven young researchers coming from different fields.